Blood crime : an original Hollows graphic novel - Harrison, Kim, 1966- (Del Rey Ballantine Books, 2012)
"You can't tell the story of how it all began for supernatural cops Ivy Tamwood and Rachel Morgan without telling how it all nearly ended. The fiery living vampire and erstwhile earth witch never asked to be paired up in the first place. And having to work Inderland Security'scrummiest beat--busting two-bit paranormal street punks--sure didnt sweeten the deal. But when it counts, Ivy and Rachel always have each other's backs. They'd better--because someone just hung targets on both of them."--Amazon.com.